Síndrome de Vogt-Koyanagi-Harada en niños - Velásquez R., Víctor; Araya C., Javiera; Pérez V., Fernanda; Morales E., Sergio; Fuentes G., Esteban; Romero C., Pablo (Revista Hospital Clínico Universidad de Chile, 2017)
Introduction: Vogt-Koyanagi-Harada (VKH) syndrome is a systemic inflammatory disease that causes chronic and bilateral granulomatous panuveitis, usually described in adults. Objectives: To describe manifestations and complications of VKH in pediatric patients. Methods: Retrospectivedescriptive study upon patients less than 14 years-old with VKH, attended from January 1985 to July 2010 in three different centers. Results: A total of 17 patients (34 eyes) were studied; 9 (53%) female. The mean age was 10.8 years-old. Among extraocular manifestations; neurological (71%), dermatological (29%) and auditive (24%) signs were observed. Ocular findings included optic-disc involvement (94%), anterior uveitis (79%), choroiditis (77%), serous retinal detachment (71%) and vitritis (71%). Initial visual acuity (VA) was ≤0.05 in 47% of cases and ≥0.6 in 12% of patients. 71% presented complications: glaucoma (20 eyes), sinechiae (10 eyes), maculopathy (6 eyes) cataract (5 eyes) and ptisis bulbi (1 eyes). 35% received only corticosteroids and 65% inmunosupressive drugs. After treatment, 6% had VA ≤0.05 and 59% ≥0.6. Ten patients (59%) recurred: 30% compromising posterior pole, and 50% recurred >3 times. Conclusions: VKH in children is infrequent. It presents with optic-disc involvement and complications of posterior pole. It requires a high degree of suspicion, quick evaluation and early treatment, which include inmunosupressive and extended corticosteroid therapy. Nevertheless, a high rate of recurrence is seen among this group of patients.